The 5-minute pediatric consult - Schwartz, M. William , 1935- (5-minute consult series, 2012)
"The 5 Minute Pediatric Consult provides immediate, practical advice on problems seen in infants, children, and adolescents. More than 450 diseases and conditions are covered in the fast-access two-page outline format that makes The 5-Minute Consult Series titles so popular among busy clinicians. Other features include a Chief Complaints section addressing the workup and treatment of 50 signs and symptoms, plus a medication index, syndromes glossary, surgical glossary, laboratory values, and tables all for quick reference saving you time and helping to treat your patients more efficiently.In this sixth edition, the 5 Minute Pediatric Consult also offers free 30 day access to the 5minuteconsult Pediatric website -- a clinical decision support tool -- that can be accessed by the health care providers to address questions on-the-go via website or mobile.New Features: New topics for this edition include: Amenorrhea, Asberger Syndrome, Dental Trauma, Head banging, Mental Retardation, Narcolepsy, Obsessive Compulsive Disorder, Separation Anxiety and Social Anxiety Free 30 Day Access to the 5minuteconsult Pediatric Website Includes More than 450 diseases and conditions to support your patient care decisions Patient education handouts from AAP to help educate your patients Hundreds of Images from Chung's "Visual Diagnosis and Treatment in Pediatrics" and other reputable sources to provide you with quick visual guidance Immunization schedules and charts at your fingertips to save you time from searching Content is optimized for handheld devices so you have access to the content anytime, anywhere Updates to content made on a regular basis to keep you abreast of the latest content Visit 5minuteconsult.com and click on the "go to pediatric consult tab" to learn more about your free access and begin using today!"--Provided by publisher.